Multi-stage compound real options valuation in residential PV-Battery investment. (15th January 2020) - Ma, Yiju; Swandi, Kevin; Chapman, Archie C.; Verbič, Gregor
Abstract: Strategic valuation of efficient and well-timed network investments under uncertain electricity market environment has become increasingly challenging, because there generally exist multiple interacting options in these investments, and failing to systematically consider these options can lead to decisions that undervalue the investment. In our work, a real options valuation (ROV) framework is proposed to determine the optimal strategy for executing multiple interacting options within a distribution network investment, to mitigate the risk of financial losses in the presence of future uncertainties. To demonstrate the characteristics of the proposed framework, we determine the optimal strategy to economically justify the investment in residential PV-battery systems for additional grid supply during peak demand periods. The options to defer, and then expand, are considered as multi-stage compound options, since the option to expand is a subsequent option of the former. These options are valued via the least squares Monte Carlo method, incorporating uncertainty over growing power demand, varying diesel fuel price, and the declining cost of PV-battery technology as random variables. Finally, a sensitivity analysis is performed to demonstrate how the proposed framework responds to uncertain events. The proposed framework shows that executing the interacting options at the optimal timing increases the investment value. Highlights: A compound real options model is proposed to evaluate a PV-battery investment. Optimal timing of the compound option execution maximizes the investment value. Interactive option valuation provides benefits beyond independent valuation. Sensitivity analysis shows how the model responds to changing state variables.